ANALISIS TINGKAT KERUSAKAN DAN STRATEGI PENGELOLAAN MANGROVE DI KAWASAN SUAKA PERIKANAN GILI RANGGO TELUK SERIWE KABUPATEN LOMBOK TIMUR NUSA TENGGARA BARAT - Subhan, Mohammad; Antara, Made; Astarini, Ida Ayu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 8 No 1 (2014), 2014)
GiliRanggoFisheryReserve Areais one of conservation areaestablished throughthe Regional Regulationof East Lombok, West Nusa Tenggara number10year 2006 onRegionalMarine ProtectedArea Management(RMPAM). Sincethe enactment ofthereserve fisheries zone, managementsystemis not yet optimizedeitheronthe mangrove protected areasandstakeholdercommitmentto theconservationefforts ofthemangrove resource. The purpose ofthis study were 1) to analyzethe extent of mangrove damageinGiliRanggoFisheryReserve Area, 2) to find out perceptions of stakeholderson the management ofmangrovesin the area of GiliRanggoFishery at the reserve area, 3) to formulatea sustainablemanagementstrategyinvolvingallstakeholders. This study useda combination ofqualitativeandquantitativeapproaches. Data analysis methodsused include: vegetationanalysis, qualitativeanalysisandSWOT analysiskatagorik. The results showed that the destruction level of mangrove damage at GiliRanggoFishery Reserve Areaon seedlings and saplings phase are trees are relatively minor with density <50% and widespread closure> 1,500 trees/ha, whereas severely damaged represented by closure <50% and a density of <1,000 trees/ha. Mangrove vegetation in the GiliRanggoFishery Reserve Areais not classified as critical represented by the Total Value Scoring (TNS) = 370. Society supports the efforts to conserve the mangrove, as people realize the key benefits of mangroves. Violations that occurred during this due to people not knowing the rules of forbide on harvesting mangrove. The formulation of mangrove management strategies in GiliRanggoFishery Reserve Area consists of SO strategy: maximizing the primary function of mangroves and management principles tailored to the status of the area, ST strategies: increase public knowledge about environmental management and improve the economy of the community, WO strategies: increasing community involvement and increasing the studies and research in the management of mangroves in GiliRanggoFishery Reserve Area, WT strategies: joint management plans involving all stakeholders, improve supervision and monitoring
Keywords: Mangrove Damage,StrategyManagement,Vegetation,East Lombok